The relationship between the psychological awareness of the paramedic and the efficiency of emergency intervention in cases of behavioral disorders (The Review of Diabetic Studies, 2025)
This study aims to explore the relationship between paramedics' psychological awareness and the effectiveness of emergency interventions in cases of behavioral disorders. Psychological awareness refers to a first-aider's ability to recognize their own psychological state and understand and manage the psychological state of injured people during emergency situations. This research followed the descriptive method of analysis where a questionnaire guided by a structure was administered to a group of paramedics. Findings indicated that there is a positive correlation between an elevated degree of psychological awareness and high effectiveness of emergency interventions, such as better decision-making, less errors, and higher communication with behaviorally disrupted patients. The paper emphasizes the role of psychological training programs to the paramedics as an intervention to improve their professional performance and quality of emergency care.